Migraine with prolonged aura vs migraine-associated stroke: a case series. Case report - Aleksey A. Kulesh; Natalia L. Starikova; Dmitry A. Demin; Sergey Krapivin; Sergei A. Mekhriakov; Nadezhda A. Kaileva; Marina V. Lezhikova (Consilium Medicum)
The article presents three clinical cases of patients with migraine with aura and long-term focal symptoms without the formation of ischemic foci. A case of migraine-associated stroke is presented for comparison. The presented cases indicate that admission to the hospital of a patient with a history of migraine and a focal neurological deficit is a challenging clinical situation that requires individualization of diagnostic and therapeutic tactics. In the presence of a prolonged aura, CT perfusion, and diffusion-weighted magnetic resonance imaging, can contribute to an informed clinical decision. The MRI findings should be interpreted cautiously since transient cortical edema may be associated with aura prolongation. If it is impossible to differentiate reliably between migraine and stroke in a short time, intravenous thrombolysis should be performed.